Technical Specifications of Structural Health Monitoring for Highway Bridges: New Chinese Structural Health Monitoring Code - Moreu, Fernando; Li, Xiaomeng; Li, Shunlong; Zhang, Dongyu (Frontiers in Built Environment, 2018)
Governments and professional groups related to civil engineering write and publish standards and codes to protect the safety of critical infrastructure. In recent decades, countries have developed codes and standards for Structural Health Monitoring (SHM). During this same period, rapid growth in the Chinese economy has led to massive development of civil engineering infrastructure design and construction projects. Consequently, China has become the leading country of civil engineering. In 2016, the Ministry of Transportation of the People’s Republic of China published a new design code for SHM systems for large highway bridges. This document is the first technical SHM code by a national government that enforces sensor installation on highway bridges. This paper summarizes the existing international technical SHM codes for various countries and compares them with the new SHM code required by the Chinese Ministry of Transportation. The paper outlines the contents of the new Chinese SHM code and explains its relevance for the safety and management of large bridges in China, introducing key Chinese-US SHM vocabulary, definitions and technical significance. Finally, this paper discusses the implications for the design and implementation of a future US SHM code, with suggestions for similar efforts in other countries and governments.